Être femme dans la recherche. Éléments de réflexion - Fougeyrollas-Schwebel, Dominique; Zaidman, Claude (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2003)
Number: 11 Publisher: Université Paris Diderot – Paris 7
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; inégalités; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

Unbearable weight: Feminism, western culture, and the body - Bordo, Susan (University of California Press, 2003)
Susan Bordo untangles the myths, ideologies, and pathologies of the modern female body. Bordo explores our tortured fascination with food, hunger, desire, and control, and its effects on women's lives
Keywords: 2000 à aujourd'hui; 2000-2009; corps; cours; discipline; fem1000; image corporelle; occident; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; études culturelles

Handicap, recherche et changement social. L’émergence du paradigme émancipatoire dans l’étude de l’exclusion sociale des personnes handicapées - Boucher, Normand (Lien social et Politiques, 2003)
Le champ du handicap a subi de profondes transformations au cours des quatre dernières décennies dans la majorité des sociétés postindustrielles. Ce phénomène, qui influence les approches théoriques et la recherche à l’intérieur des sciences sociales, a fait surgir un nouveau paradigme émancipatoire basé sur une remise en cause des rapports entre le chercheur et le « sujet d’étude ». Dans cet article, nous explorons le développement de ce paradigme en nous appuyant sur l’expérience britannique, et nous discutons de son apport à la compréhension du handicap et des politiques sociales en abordant la question du rôle et de la position des acteurs au sein de la pratique de recherche
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; EDI; approches et analyses; capacitisme; corps; cours; discipline; histoire et politique; premier cycle; périodes historiques; ressource en ligne; ré; santé; sciences humaines; sex1920; sociologie; systèmes d'oppressions; thématiques; études critiques du handicap

La fin de la domination (masculine) Pouvoir des genres, féminismes et post-féminisme queer - Bourcier, Sam (M.H) (Multitudes, 2003)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; europe; fem1000; france; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques

Le discours des défenseurs des droits des hommes sur la violence conjugale: Une analyse critique - Brodeur, Normand (Service social, 2003)
Se disant victimes d'injustices non reconnues, les défenseurs des droits des hommes dénoncent le discours féministe sur la violence masculine et les politiques sociales mises en place depuis vingt ans pour combattre la violence conjugale. Cet article résume leurs principaux arguments à partir d'une analyse de contenu de trois ouvrages publiés au Québec. La seconde partie de l'article situe ces arguments à l'intérieur des controverses autour de la définition de la violence, de la violence des femmes et du maintien d'un équilibre entre les droits des victimes et ceux des personnes accusées devant les tribunaux. Elle fait aussi état de données qui remettent en question les thèses des défenseurs des droits des hommes sur la symétrie générale de la violence entre les sexes et sur la discrimination systématique dont les hommes seraient victimes au sein du système judiciaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; antiféminisme; approches et analyses; canada; couple; cours; discipline; premier cycle; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; trs1205; violences

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Section: x, 338 p. ; 24 cm Table des matières Introduction / Rory Dicker and Alison Piepmeier The "big lie": false feminist death syndrome, profit, and the media / Jennifer L. Pozner In a word, Baywatch / Susannah B. Mintz. Reviving Lolita ; or, because junior high is still hell / Alyssa Harad "That's not fair!" : nurturing girls' natural feminism / Nancy Gruver Voices and visions : a mother and daughter discuss coming to feminism and being feminist / Roxanne Harde and Erin Harde Please–stop thinking about tomorrow : building a feminist movement on college campuses for today / Sarah Boonin Who's the next Gloria? : the quest for the third wave superleader / Jennifer Baumgardner and Amy Richards Buffy the vampire slayer : the next generation of television / Michele Byers Third World, third wave feminism(s) : the evolution of Arab American feminism / Susan Muaddi Darraj Feminism's family problem : feminist generations and the mother-daughter trope / Astrid Henry Do the ladies run this– ? Some thoughts on hip-hop feminism / Gwendolyn D. Pough The transfeminist manifesto / Emi Koyama Hearing the daughter voice : The Bat Kol as Rrrabbi Grrrl / Alana Suskin Rocking the gender order / Mimi Schippers Pranks and fake porn : doing feminism my way / Kristina Sheryl Wong Afterword / Katha Pollitt and Jennifer Baumgardner.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague

Dictionnaire des cultures gays et lesbiennes - Eribon, Didier; Haboury, Frédéric; Lerch, Arnaud (Larousse, 2003)
Dictionnaire illustré et international consacré aux cultures gays et lesbiennes contemporaines (depuis la fin du XIXe siècle). Plus de 570 articles(2 millions de signes en tout), dont 50 dossiers thématiques, qui couvrent tous les aspects du sujet : - références culturelles et artistiques communes (d'Absolutely Fabulous à Virginia Woolf, de Pedro Almodóvar à Andy Warhol.), - associations (Act Up.), - théoriciens (Michel Foucault.), - événements (Lesbian and Gay Pride.), - mours et modes de vie (sida, sexualités.), - aspects légaux (couple, adoption.), - gay and lesbian studies (histoire, sociologie, queer theory.), etc.
Section: 548 pages : illustrations (certaines en couleur), photogr. (certaines en couleur) ; 27 cm
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; queer; sexualité; soc2014; thématiques; études gaies et lesbiennes

Intellectuelle ou militante? Le serpent de mer fait son numéro - Kraus, Cynthia; Malbois, Fabienne; Messant, Françoise; Pannatier, Gaëlle; Perrin, Céline (Nouvelles Questions Féministes, 2003)
https://nouvellesquestionsfeministes.ch
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; thématiques

L'union civile: nouveaux modèles de conjugalité et de parentalité au 21e siècle : actes du colloque du Groupe de réflexion en droit privé - Lafond, Pierre-Claude; Lefebvre, Brigitte; Université du Québec à Montréal Groupe de réflexion en droit privé. (Éditions Y. Blais, 2003)
Textes présentés lors d'un colloque organisé par le Groupe de réflexion en droit privé et tenu à la Faculté de science politique et de droit de l'Université du Québec à Montréal, le 10 octobre 2002.
Section: xiv, 399 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits; histoire et politique; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Intersexe et transsexualités : Les technologies de la médecine et la séparation du sexe biologique du sexe social - Löwy, Ilana (Cahiers du Genre, 2003)
Le sexe social est construit sur un mode binaire. Par contre, le sexe biologique se présente comme un continuum, avec, aux deux extrêmes, les « sexes biologiques » clairement définis et, au milieu, une large gamme de situations intermédiaires — des individus « intersexe ». De tels individus remettent en cause nos certitudes sur la stabilité des catégories « homme » et « femme ». Cet article trace l’histoire des interventions médicales ayant pour but de corriger l’anomalie de l’intersexe et de produire des êtres humains dont le corps ne remet pas en cause la bipolarité du féminin et du masculin. Il suit les débats sur les liens supposés entre intersexualité et homosexualité puis expose la transition du traitement de l’intersexualité à celui de la transsexualité. Il étudie enfin le rôle des nouvelles techniques de la médecine dans la séparation entre le « sexe » et le « genre ». La possibilité de moduler les paramètres du « sexe biologique » permet alors une réflexion sur le « sexe social » comme variable indépendante des structures biologiques.
Number: 1 Publisher: L'Harmattan
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Multitudes queer : notes pour une politique des "anormaux" - Preciado, Paul B. (Multitudes, 2003)
Cet article traite de la formation des mouvements et des théories queer, de la relation qu’ils entretiennent avec les féminismes et de l’utilisation politique qu’ils font de Foucault et de Deleuze. Il explore aussi les avantages théoriques et politiques que procure la notion de "multitudes" par rapport à celle de "différence sexuelle" pour la théorie et le mouvement queer. À la différence de ce qui se passe aux Etats-Unis, les mouvements queer en Europe, s’inspirent des cultures anarchistes et de l’émergence des cultures transgenres pour contrer l’"Empire Sexuel" notamment en proposant une dés-ontologisation des politiques des identités. Plus de base naturelle ("femme", "gay", etc.) qui puisse légitimer l’action politique. Importance non de "la différence sexuelle" ou de "la différence des homosexuels (le) s", mais des multitudes queer. Une multitude des corps : corps transgenres, hommes sans pénis, gouines garous, cyborgs, femmes butchs, pédés lesbiennes... La "multitude sexuelle" apparaît ainsi comme le sujet possible de la politique queer.
http://www.lespantheresroses.org/textes/multitudes_queer.htm
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; fem1000; philosophie politique; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques

La scission politique du féminisme international sur la question du “ trafic des femmes ” vers la “ migration ” d’un certain féminisme radical ? - Toupin, Louise (Recherches féministes, 2003)
Cet article donne un aperçu de l’argumentation qui met en lumière et différencie les principales coalitions internationales féministes luttant contre ce qui est couramment appelé le « trafic des femmes ». L’argumentation mise en évidence ne touche que la définition du phénomène et le différend qui sépare les coalitions sur le sujet, ainsi que leurs stratégies respectives pour l’éradiquer. L’auteure souligne en conclusion certains tangentes du féminisme radical qui, à son avis, se voient désormais remises en cause à l’occasion du débat sur les migrations des femmes. Ce débat entraînera-t-il, à son tour, se demande-t-elle, la migration d’un certain féminisme radical ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; histoire du féminisme; histoire et politique; intersectionnalité; miitance; patriarcat; premier cycle; prostitution; périodes historiques; ressource en ligne; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; traite des femmes; travail; travail du sexe; violences

Les courants de pensée féministe - Toupin, Louise; Centre de documentation sur l'éducation des adultes et la condition féminine (J.-M. Tremblay, 2003)
“ Les courants de pensée féministe ” (1998). Un texte publié dans l'ouvrage Qu'est que le féminisme? Trousse d'information sur le féminisme québécois des vingt-cinq dernières années, Montréal, Centre de documentation sur l'éducation des adultes et la condition féminine/Relais-femmes, 1997.
https://bv.cdeacf.ca/CF_PDF//2002_17_0057.pdf
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; deuxième vague; discipline; droits des femmes*; histoire et politique; outils; patriarcat; pol4022; premier cycle; périodes historiques; régions géographiques; science politique; systèmes d'oppressions; thématiques

Queer theory and communication: from disciplining queers to queering the discipline(s) - Yep, Gust A.; Lovaas, Karen; Elia, John P. (Harrington Park Press, 2003)
Get a queer perspective on communication theory! Queer Theory and Communication: From Disciplining Queers to Queering the discipline(s) is a conversation starter, sparking smart talk about sexuality in the communication discipline and beyond. Edited by members of "The San Francisco Radical Trio," the book integrates current queer theory, research, and interventions to create a critical lens with which to view the damaging effects of heteronormativity on personal, social, and cultural levels, and to see the possibilities for change through social and cultural transformation. Queer Theory and Communication represents a commitment to positive social change by imagining different social realities and sharing ideas, passions, and lived experience. As the communication discipline begins to recognize queer theory as a vital and viable intellectual movement equal to that of Gay and Lesbian studies, the opportunity is here to take current queer scholarship beyond conference papers and presentations. Queer Theory and Communication has five objectives: 1) to integrate and disseminate current queer scholarship to a larger audience-academic and nonacademic; 2) to examine the potential implications of queer theory in human communication theory and research in a variety of contexts; 3) to stimulate dialogue among queer scholars; 4) to set a preliminary research agenda; and 5) to explore the implications of the scholarship in cultural politics and personal empowerment and transformation.
Section: xxx, 415 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; communication; cours; disicpline; premier cycle; périodes historiques; queer; régions géographiques; soc2014; systèmes d'oppressions; thématiques; états-unis